A new quaternary stratigraphy of the Kallang River Basin, Singapore: implications for urban development and geotechnical engineering in Singapore - Chua, Stephen (2022)
The Quaternary stratigraphy of many coastal areas in Southeast Asia is poorly understood. Developing a detailed framework is important as many coastal cities are built on these unconsolidated coastal-marine sediments. This study reviews the current understanding of Quaternary deposits in the Kallang River Basin, Singapore, using 161 boreholes to create 14 cross-sections and a 3D geological model. The dataset is augmented with a ~38.5 m long sediment core obtained from Marina South (1.2726°N, 103.8653°E), and a previous record from Geylang (1.3137°N; 103.8917°E), to provide age constraints and stratigraphic reference. A new Quaternary stratigraphic framework for Singapore is presented here, constrained by new radiocarbon and Optically Stimulated Luminescence (OSL) dating, and identify palaeo-features that record the geomorphic and sedimentary evolution of the basin. Fluvial deposits of Pleistocene age are uncomfortably overlain by littoral/tidal sands and subsequently marine clay possibly during Marine Isotope Stage (MIS) 5e (~125 ka BP). Subsequent subaerial exposure and weathering of the marine clay during the last interglacial produced a ‘stiff clay’ layer. The stiff clay is unconformably overlain by Holocene transgressive sands and peats from ~9.5 ka BP, followed by marine clays with a maximum basal age of ~9.2 ka BP. Regressive sandy/peat units were subsequently deposited beginning ~6 ka BP. Here the new Quaternary stratigraphic framework for Singapore is presented, as well as provide important constraints on the regional sea-level history and geomorphological evolution of Singapore's southern coast from MIS 5e to present. The work also highlights the complexities of geoengineering work in such subsurface terranes.